(untitled) - Misiti, Michel (London ; Newport Beach, CA, 2007)
This book is introduction to wavelet technology helps engineers master the basic techniques for using wavelets in such applications as image compression, turbulence, human vision, radar, and earthquake prediction. Among the topics covered are the mathematical framework for wavelets, the various wavelet families, signal denoising, and image processing
Keywords: Wavelets (Mathematics),Sóng giao thoa (Toán học)